Report of visual strategies applied on-line course and its impact in the acquisition of significant learning in adult students - Ignacio Rafael Jaramillo Urrutia (Corporación Universitaria Minuto de Dios, 2007)
This article presents the final report of the project results from the exploratory research and the visual strategies applied in online courses and its impact on the acquisition of the significant learning in adult learners. The aim of the investigation focused on determining the extent in which a strategy implemented in a visual on-line course promotes positively or negatively the acquisition of significant learning in any adult student. Because of that, there were applied theories and significant conceptual maps by Joseph Novak and David Ausubel, as well as the teaching and visual signaling by Jorge Mendez, in the design of a fast prototype course online learning.